Drivers, advances, and significance of measures for effective circular food packaging - Poças, Fátima; do Céu Selbourne, Maria (Frontiers in Sustainable Food Systems, 2023)
This paper provides an overview of the fundamental aspects pertaining an effective circular packaging. The main challenges of food packaging systems to comply with the principles of circular economy are addressed. A perspective of the technical issues that drive packaging developments is given, and the main barriers and limiting factors for packaging waste reduction, reusing, and recycling are discussed, particularly as applied to plastic packaging. The state-of-art of recycling plastics for food contact is presented, as well as the gaps for safety assurance. The relevance of consumer and the impact on the whole chain is discussed under the framework of citizens motivation, ability, and opportunity to engage the different measures. Finally, the main measures under the scope of the packaging and waste regulation, and foreseen amendments, and of the plastics recycling directive are briefly presented.